Piil Pesengiri: Unsur Budaya Lokal Lampung Dalam Konsep Moderasi Beragama Prespektif Tafsir Al-Misbah - Istiqomah; Kiki Muhammad Hakiki; Abuzar Alghifar (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines how culture can play an active role in efforts to moderate religion, namely through piil pesenggiri which is one of the local cultures of the Lampung community. This role is then analyzed based on the perspective of the Qur'an through the Tafsir Al-Misbah by an Indonesian mufassir, Quraish Shihab. This is done considering the importance of integrating cultural values ​​in social and religious contexts. The purpose of this study is to explore and analyze how local cultural values ​​can be internalized in the practice of religious moderation. The method used is the Mix Method which combines two types of research, namely field research and library research, descriptions of interview results as field data and results from library research. The main findings show that the Lampung community has a good understanding of the urgency of religious moderation. However, the implementation of these moderation values ​​at the practical level still requires further strengthening. This study also identifies that local cultural values ​​have great potential in supporting religious moderation in society. In addition, this study provides insight into the dynamic relationship between culture and religion, and recommends a number of practical recommendations that can be used as a basis for policies that support harmonization between the two.